Demonstration of Eight-Sensor Sagnac Fiber-Optic Hydrophone Array with Alternative Quadrature Phase Bias and Response Equalization Demodulation Algorithm - Zhao, Delong; Wang, Ke; Yang, Shuolin; Xie, Wenjie; Chen, Yuzhong; Yang, Jie; Song, Zhangqi; Sun, Zhaohua (Photonics, 2025)
The Sagnac interferometer-based fiber-optic hydrophone (S-FOH) exhibits a frequency-dependent response, causing the output signal to deviate from the original acoustic signal, with severe cases leading to signal distortion. A response equalization demodulation algorithm is demonstrated to recover high-fidelity acoustic signals from interference phase signals. An eight-sensor S-FOH array featuring an alternative quadrature phase bias scheme is demonstrated, and experimental verification of the response equalization demodulation algorithm is performed. The temporal relationship of phase modulation pulses and sampling light pulses is analyzed, and a demodulation algorithm is introduced to obtain the phase difference of the Sagnac interferometer. The acoustic pressure sensitivity is equalized to be flat with an average of −135.0 ± 0.4 dB from 10 to 2032 Hz. The pulse response of the S-FOHA after the equalization algorithm is highly similar to the PZT hydrophone output signal, with a correlation coefficient of 0.987.